Preferences for Using the Quick Response Code Indonesia Standard (QRIS) Payment Method for Accounting Education Students at Universitas Muhammadiyah Surakarta - Aprilia Ayu Lestari; Surya Jatmika (Universitas KH. Abdul Chalim Mojokerto, 2024)
On January 1st, 2020, Bank Indonesia officially released and implemented the Quick Response Code Indonesia Standard (QRIS) payment method. Although some students still use cash as a means of payment, many of them are switching to QRIS to make transactions. This study aims to analyze preferences for using QRIS, factors that influence the use of QRIS, and obstacles faced by Accounting Education Study Program students in its use. The method used in this research is a case study, with data collection techniques through observation, interviews, and documentation. To ensure data validity, researchers applied triangulation techniques by collecting information from the same source through various methods. The data analysis process includes data reduction, data presentation, and conclusion drawing. The results showed that students of the Accounting Education Study Program tend to choose QRIS to meet their daily needs, such as buying food, clothing, skin care products, boarding house equipment, and cooking ingredients. They consider QRIS as a better payment tool because of the convenience, speed, and practicality factors. However, the obstacles faced, such as internet network instability and running out of quota, do not prevent them from continuing to use QRIS as the main payment method.